Investigating the association between stress, saliva and dental caries: a scoping review - Svetlana Tikhonova; Linda Booij; Violet D'Souza; Karla T. B. Crosara; Walter L. Siqueira; Elham Emami (BMC, 2018)
Abstract Background This scoping review addressed the question 'what do we know about stress-related changes in saliva and dental caries in general population?' Methods The review was conducted using electronic searches via Embase, MEDLINE, PsycINFO, CINAHL and WoS. All published human studies with both observational and experimental designs were included. Two reviewers independently reviewed eligible articles and extracted the data. The studies' quality was assessed using the Effective Public Health Practice Project Quality Assessment Tool. Results Our search identified 232 reports, of which six were included in this review. All six studies were conducted in children and used salivary cortisol as stress marker. The studies varied by design, types of stressors, children's caries experience, methods of saliva collection. Four studies reported a positive association between saliva cortisol levels and caries (p < 0.05) while the other two reported no association (p > 0.05). The quality of the included studies was weak to moderate. Conclusions There is lack of evidence about an association between stress-related changes in saliva and caries. Well-designed longitudinal studies with rigorous measurement technics for stress, saliva and dental caries are necessary. This will help to generate new insights into the multifactorial etiology of caries and provide evidence for a rational method for its control.